2022
DOI: 10.1136/gutjnl-2022-327075
|View full text |Cite
|
Sign up to set email alerts
|

Autologous regulatory T-cell transfer in refractory ulcerative colitis with concomitant primary sclerosing cholangitis

Abstract: ObjectiveUlcerative colitis (UC) is a chronic, debilitating immune-mediated disease driven by disturbed mucosal homeostasis, with an excess of intestinal effector T cells and an insufficient expansion of mucosal regulatory T cells (Tregs). We here report on the successful adoptive transfer of autologous, ex vivo expanded Tregs in a patient with refractory UC and associated primary sclerosing cholangitis (PSC), for which effective therapy is currently not available.DesignThe patient received a single infusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…IBD is a chronic and nonspecific inflammatory condition characterized by ulceration and damage to the colonic mucosa. 20 Bifidobacterium strains are essential for infants as they promote intestinal homeostasis and immune system development. Bifidobacterium strains, which are simultaneously most abundant in the infant's gut, can be vertically transmitted through breast milk, resulting in a higher presence of Bifidobacterium in breastfed infants compared to nonbreastfed counterparts.…”
Section: ■ Discussionmentioning
confidence: 99%
“…IBD is a chronic and nonspecific inflammatory condition characterized by ulceration and damage to the colonic mucosa. 20 Bifidobacterium strains are essential for infants as they promote intestinal homeostasis and immune system development. Bifidobacterium strains, which are simultaneously most abundant in the infant's gut, can be vertically transmitted through breast milk, resulting in a higher presence of Bifidobacterium in breastfed infants compared to nonbreastfed counterparts.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Newly developed therapies, like IL-23 inhibitors, TLR-9 agonists, sIL-6R Therapies in Ulcerative Colitis inhibitors, and upregulators of micro-RNA, not only offer novel treatment approaches but also enable us to gather more insights into disease pathogenesis. Currently conducted cell-based therapy trials that investigate effectiveness of regulatory T-cell transfer might further expand our treatment approaches for the benefit of patients [43]. Combination or sequential use of advanced therapies warrants further investigation, as they might offer heightened efficacy, but long-term safety needs to be studied in these endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical research has demonstrated strong potential for Treg-based immunotherapies in the prevention or treatment of graft-versus-host disease, organ transplant rejection, and a variety of autoimmune diseases, such as type 1 diabetes, multiple sclerosis (MS), celiac disease, and inflammatory bowel disease [6][7][8][9][10][11]. In these therapies, Tregs-either polyclonal or genetically engineered to express antigen-specific T-cell receptors (TCR-Tregs) or chimeric antigen receptors (CARs-Tregs)-are expanded ex vivo prior to reinfusion as an adoptive cell therapy (ACT) [7,9,11].…”
Section: Introductionmentioning
confidence: 99%